Theory-based correlates of cannabis use and intentions among US and Israeli adults: a mixed methods study - Yuxian Cui; Cassidy R. LoParco; Yael Bar-Zeev; Zongshuan Duan; Hagai Levine; Lorien C. Abroms; Yan Wang; Amal Khayat; Carla J. Berg (BMC, 2023)
Abstract Background In the US and Israel, non-medical ('recreational') cannabis use is illegal at the national level; however, use rates are high and decriminalization and legalization is spreading. Thus, theory-based intervention efforts, especially for youth prevention, are crucial. Methods This mixed-methods study of adults in the US (n = 1,128) and Israel (n = 1,094) analyzed: 1) cross-sectional survey data (Fall 2021) to identify theory-based correlates (risk perceptions, social norms) of past-month cannabis use, next-year use intentions, and intentions to use in the home or among children if non-medical cannabis was legal, using multivariable regression; and 2) qualitative interviews regarding perceptions of cannabis policies and use (US n = 40, Israel n = 44). Results 16.7% reported past-month use; 70.5%, 56.3%, and 82.6% indicated "not at all likely" regarding next-year use and use in the home and among children if legal. Lower perceived risk and greater social norms were associated with past-month use, greater use intentions, and greater intentions to use in the home or among children. Past-month use was more prevalent among US (vs. Israeli) participants (22.0% vs. 11.2%); however, in multivariable regression controlling for past-month use, being from Israel was associated with greater use intentions (next-year; in the home/among children). Qualitative themes indicated: concerns about use (e.g., increasing use, health risks, driving-related risks) and legalization (e.g., impact on society/economy, marketing), and perceived benefits of use (e.g., medical) and legalization (e.g., access/safety, economic, individual rights). Conclusions Despite differences in cannabis perceptions and use across countries, perceived risk and social norms are relevant intervention targets regardless of sociopolitical context.